Evaluation of Double-Vacuum Saturation in Triaxial Testing of Compacted Clay: A Comparison with Back-Pressure Methods - Muhammad Riza; H. Nawir; E. Rismantojo; Fourier D. E. Latief (Civil Engineering Journal, 2026)
Achieving full saturation in consolidated triaxial testing is challenging, especially for compacted and residual soils with low water content and complex microstructures. Conventional back-pressure saturation can cause disturbance and leaching, leading to unreliable results. This study evaluates the double-vacuum (DV) method to reduce sample disturbance and better preserve microstructure during testing of compacted kaolin clay. Two methods—back pressure (NV) and double-vacuum (DV)—were compared using the consolidated undrained triaxial test and micro-CT imaging. The DV method reached a Skempton B-value ≥ 0.95 at lower pressure (150-200 kPa) in 8 hours, while NV needed up to 450 kPa and 50 hours. The DV approach halved axial and radial deformation and resulted in lower changes in void ratio (De/e0 ≈ 0.055), indicating improved sample integrity. Micro-CT showed a more uniform pore distribution and lower residual porosity (0.43%) versus NV (1.04%). These results suggest the DV method is a more reliable, less intrusive way to prepare fine-grained soils for triaxial testing, with significant implications for geotechnical labs, especially where high-pressure systems are limited.